Bank loans or bonds: some lessons of historical experience - ARNDT, H.W.; DRAKE, P.J. (PSL Quarterly Review, 2013)
The continuing international debt crisis has led some commentators to suggest that bond markets rather than banks would be a more appropriate method of financing development in the Third World. It has been suggested that the bond market is a more appropriate mechanism for assessing risk and channelling long-term development funds. In fact, until the 1930s, most development finance was provided by the bond market, and it was only the collapse of capital markets in the 1930s that stopped this function from continuing. By examining the historical experience, the authors consider the potential for bond financing and the conditions which would be necessary for its revival. JEL: F34, G12, N24,